Assessing the fidelity of the independently getting up off the floor (IGO) technique as part of the ReTrain pilot feasibility randomised controlled trial for stroke survivors. Issue 25 (4th December 2022) - Hollands, Laura; Calitri, Raff; Warmoth, Krystal; Shepherd, Anthony; Allison, Rhoda; Dean, Sarah; ,; ,
Abstract: Purpose: Hemiparesis and physical deconditioning following stroke lead to an increase in falls, which many individuals cannot get up from. Teaching stroke survivors to independently get off the floor (IGO) might mitigate long-lie complications. IGO was taught as part of a community-based, functional rehabilitation training programme (ReTrain). We explore the feasibility of teaching IGO and assess participant's level of mastery, adherence, and injury risk. Materials and methods: Videos of participants ( n  = 17) performing IGO at early, middle, and late stages of the ReTrain programme were compared to a manualised standard. A visual, qualitative analysis was used to assess technique mastery, adherence, and injury risk. Results: Most participants (64%) achieved independent, safe practice of IGO. A good (73%) level of adherence to IGO and low incidence of risk of injury (6.8%) were observed. Deviations were made to accommodate for non-stroke related comorbidities. Conclusions: IGO was successfully and safely practised by stroke survivors including those with hemiparesis. Trainers should be aware of comorbidities that may impede completion of IGO and modify teaching to accommodate individual need. Further research should assess if IGO can be utilised by individuals who have other disabilities with unilateral impairments and whether IGO has physical, functional and economic benefit. Implications for rehabilitation: Falls are common in stroke survivors, and many are unable to get up despite being uninjured, leading to long-lie complications or ambulance call-outs but non-conveyance to hospital. Teaching the independently getting up off the floor (IGO) technique to stroke survivors was possible for those with or without hemiparesis, and remained safe despite modifications to accommodate an individual's needs. Individual assessment is needed to check if a stroke survivor is suitable for learning IGO including, but not limited to, their ability to safely get to the floor and to temporarily stand (without support) at the end of the technique.